The agriculture we promote : IICA Delegation in Canada: country strategy 2016-2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
Through the Country Strategy, IICA’s Delegation in Canada seeks to respond to the country’s needs as well as those of others in the hemisphere, determining results to be achieved by 2018 and strategies, actions and activities to reach the established goals, as well as the method used to measure progress.